2020
DOI: 10.21203/rs.3.rs-55459/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of APOE ε4 genotype on amyloid-β and tau accumulation in Alzheimer’s disease

Abstract: Background: To assess effects of apolipoprotein E (ApoE) ε4 genotype on Aβ and tau burden and their longitudinal changes in Alzheimer’s disease (AD) spectrum.Methods: Among 272 individuals who underwent PET scans (18F-florbetaben for Aβ and 18F-flortaucipir for tau) and ApoE genotyping, 187 individuals completed 2-year follow-up PET scans. After correcting for partial-volume effect, we compared the standardized uptake value ratio (SUVR) for Aβ and tau burden between the ε4+ and ε4- groups. By using a linear mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…This could be attributed to fewer number of ApoE ε4 carrier homozygote subjects relative to ApoE ε4 carrier heterozygotes (1‐copy of ApoE ε4 allele) and noncarriers within the population. Based on literature evidence, physiological relevance, along with the significant improvement in OFV, both homozygote and heterozygote carriers (as well as noncarriers) were included as covariates, despite the large CI for carrier homozygote 10–12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to fewer number of ApoE ε4 carrier homozygote subjects relative to ApoE ε4 carrier heterozygotes (1‐copy of ApoE ε4 allele) and noncarriers within the population. Based on literature evidence, physiological relevance, along with the significant improvement in OFV, both homozygote and heterozygote carriers (as well as noncarriers) were included as covariates, despite the large CI for carrier homozygote 10–12 …”
Section: Resultsmentioning
confidence: 99%
“…Based on literature evidence, physiological relevance, along with the significant improvement in OFV, both homozygote and heterozygote carriers (as well as noncarriers) were included as covariates, despite the large CI for carrier homozygote. [10][11][12] The relevance of these associated covariates is shown in Figure 3a and Figure 3b. Overall, it can be inferred that, except for age, all other identified covariates had a minimal effect on PK-PD parameters (Baseline, E max , and K out ) or as measured using ∆SUVR at steady-state.…”
Section: Poppk-pd Modelmentioning
confidence: 99%
“…However, it is important to note that this work was performed using standard T1 isotropic 1 mm 3 images, where subfields were not investigated. Recently, several studies showed higher MTL tau-PET uptake in APOE ε4 carriers in comparison to non-carriers (Ramanan et al, 2019; Baek et al, 2020; Pereira et al, 2020; Therriault et al, 2020; La Joie et al, 2021; Salvadó et al, 2021). Note that while the APOE ε4 allele is thought to promote tau pathology, the mechanism underlying these effects may be indirect, mediated by APOE effects on microglia (Serrano-Pozo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation, however, is that our dataset shows an enrichment of APOE ε4 carriers with MCI and dementia over cognitively normal counterparts. Regardless, this may reflect APOE ε4 carriers' increased neuropathological burden [57,58],…”
Section: Discussionmentioning
confidence: 99%